Value for money: Getting Europe's trade and IPR policy right - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2011)
The role of intellectual property rights for the world economy has increased over the past decades. Industrial countries have climbed the value-added chain by sourcing labourintensive production from emerging countries and investing substantially more human and capital resources into research and innovation. A significant, yet increasing, share of output, value-added and trade builds on innovation. Innovative sectors take up a larger share of the world economy. The amount of resources spent on research and development (R&D) have multiplied over the past decades. Competition has grown tougher as many regulations that previously protected markets and incumbents have been swept away. Technological development has speeded up the pace of imitation in the economy and shortened the life cycle of a product. (...)
Keywords: 330; EU-Politik; Immaterialgüterrechte; EU-Außenwirtschaftspolitik